Atomic layer deposition to heterostructures for application in gas sensors. (1st June 2023) - Pan, Hongyin; Zhou, Lihao; Zheng, Wei; Liu, Xianghong; Zhang, Jun; Pinna, Nicola
Highlights: Atomic layer deposition is versatile in precise design of heterostructure materials. Gas sensing performances of heterostructures engineered by ALD are reviewed. Future developments and challenges faced by ALD-designed materials are discussed. Abstract: Atomic layer deposition (ALD) is a versatile technique to deposit metals and metal oxide sensing materials at the atomic scale to achieve improved sensor functions. This article reviews metals and metal oxide semiconductor (MOS) heterostructures for gas sensing applications in which at least one of the preparation steps is carried out by ALD. In particular, three types of MOS-based heterostructures synthesized by ALD are discussed, including ALD of metal catalysts on MOS, ALD of metal oxides on MOS and MOS core–shell (C–S) heterostructures. The gas sensing performances of these heterostructures are carefully analyzed and discussed. Finally, the further developments required and the challenges faced by ALD for the synthesis of MOS gas sensing materials are discussed.